2009
DOI: 10.1007/s11200-009-0038-2
|View full text |Cite
|
Sign up to set email alerts
|

Observations of PC5 pulsations near field-aligned current regions

Abstract: Examples of long period Pc5 magnetic field pulsations near field-aligned current (FAC) regions in the high-latitude magnetosphere, observed by INTERBALL-Auroral satellite during January 11, April 11 and June 28, 1997 are shown. Identification of corresponding magnetosphere regions and subregions is provided by electrons and protons in the energy-range of 0.01100 keV measured simultaneously onboard the spacecraft. The examined Pc5 pulsations reveal a compressional character. A fairly good correlation is demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
2
1
0
Order By: Relevance
“…In that study, auroral boundaries were determined from DMSP particle data. A spatial association of Pc5 waves with magnetospheric field-aligned currents was reported by Potemra et al (1988) and Bochev et al (2009). Thus, the mentioned above results indicate that the Pc5 wave activity turns out to be closely coupled with the auroral electrodynamics comprising ionospheric electrojet, magnetospheric fieldaligned currents, and auroral particle precipitation.…”
Section: Discussion: Inference For Pc5 Wave Generation Mechanismssupporting
confidence: 52%
“…In that study, auroral boundaries were determined from DMSP particle data. A spatial association of Pc5 waves with magnetospheric field-aligned currents was reported by Potemra et al (1988) and Bochev et al (2009). Thus, the mentioned above results indicate that the Pc5 wave activity turns out to be closely coupled with the auroral electrodynamics comprising ionospheric electrojet, magnetospheric fieldaligned currents, and auroral particle precipitation.…”
Section: Discussion: Inference For Pc5 Wave Generation Mechanismssupporting
confidence: 52%
“…In that study, auroral boundaries were determined from DMSP particle data. A spatial association of Pc5 waves with magnetospheric field-aligned currents was reported by Potemra et al (1988) and Bochev et al (2009). Thus, the mentioned above results indicate that the Pc5 wave activity turns out to be closely coupled with the auroral electrodynamics comprising ionospheric electrojet, magnetospheric field-aligned currents, and auroral particle precipitation.…”
Section: Discussion: Inference For Pc5 Wave Generation Mechanismssupporting
confidence: 52%
“…that the location of the auroral oval is a preferable latitude for magnetospheric resonator excitation: namely Raspopov and Afanasieva (1982) noticed that the morning Pc5 generation region was predominantly located near the eastern edge of the westward auroral electrojet, near the equatorial boundary of the statistical position of the auroral oval; Lam and Rostoker (1978) and later Pilipenko et al (2001) showed that the positions of the westward auroral electrojet and the Pc5 wave power are closely linked to each other, and during their meandering with time the position of the Pc5 latitudinal peak remained within the borders of the auroral electrojet; Lepidi and Francia (2003), analyzing a statistical latitudinal distribution of low-frequency (1-4 mHz) geomagnetic fluctuations, concluded that the latitude of their maximum power could be considered as a marker of the auroral oval position; Simms et al (2006) showed statistically that the movement of the auroral oval correlated with Pc5 spectral power independent of changes in the solar wind and interplanetary magnetic field (IMF); and a spatial association of magnetospheric Pc5 waves with FACs was reported by Potemra et al (1988) and Bochev et al (2009). Thus, Pc5 wave activity turned out to be closely coupled with auroral electrodynamics, comprising the ionospheric electrojet, magnetospheric FACs, and auroral particle precipitation.…”
Section: A Pilipenko Et Al: Alfvén Wave Generation In the Auroramentioning
confidence: 99%